Computed tomography in nonalcoholic fatty liver disease - A useful tool for hepatosteatosis assessment? - (:unkn) unknown (SPRINGER, 2006)
The value and/or limitations of computed tomography (CT) in assessment of hepatosteatosis are not well studied in nonalcoholic fatty liver disease (NAFLD). We prospectively evaluated the accuracy of CT in assessing the amount of hepatosteatosis in NAFLD patients and the impact of demographic and histopathologic variables on CT images. Forty patients with biopsy-proven NAFLD were eligible. Of these, 10 exhibited hepatic iron overload. Liver and spleen attenuation measurements were obtained and spleen-minus-liver attenuation difference (Delta S-LA) was calculated. A good correlation between AS-LA and pathological hepatosteatosis was observed (r = 0.837, P < 0.0001). Liver iron overload did not affect this correlation, although the mean Delta S-LA was significantly lower in patients with iron overload. No correlation was detected between Delta S-LA and hepatic inflammation, fibrosis, or body mass index. We conclude that Delta S-LA derived from CT may be a useful tool for predicting the amount of hepatosteatosis in NAFLD patients as it is not affected by various individual factors.
Keywords: nonalcoholic steatohepatitis; nonalcoholic fatty liver disease; spleen-minus-liver attenuation difference; hepatic iron overload; computed tomography; HEPATIC STEATOSIS; IRON OVERLOAD; STEATOHEPATITIS